1995
DOI: 10.1002/ssu.2980110403
|View full text |Cite
|
Sign up to set email alerts
|

Laser photochemotherapy: A less invasive approach for treatment of cancer

Abstract: The effectiveness of combining surgery with chemo- and radiation therapy in treatment of human cancer provides a useful model for further development of new multimodality approaches including laser photochemotherapy. Laser endoscopy often is a useful treatment for obstructive tumors in airways, but interstitial laser fiberoptics is becoming a more precise, minimally invasive alternative for ablation of unresectable or recurrent neoplasms. Combining intratumor chemotherapy with laser energy delivery via interst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(46 citation statements)
references
References 67 publications
1
45
0
Order By: Relevance
“…The current studies corroborate and extend previous in vitro experiments that demonstrate that anthracyclines have dual properties as photodynamic agents and as cytostatic anticancer drugs [1,8,[16][17][18][19]. For example, a recent in vitro study with Adriamycin using explanted human squamous-cell carcinoma showed that exposure to the argon laser at 514 nm led to over 50% increased cytotoxicity at drug levels equal to or above 5 g/ml compared to chemotherapy alone in the dark [19].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The current studies corroborate and extend previous in vitro experiments that demonstrate that anthracyclines have dual properties as photodynamic agents and as cytostatic anticancer drugs [1,8,[16][17][18][19]. For example, a recent in vitro study with Adriamycin using explanted human squamous-cell carcinoma showed that exposure to the argon laser at 514 nm led to over 50% increased cytotoxicity at drug levels equal to or above 5 g/ml compared to chemotherapy alone in the dark [19].…”
Section: Discussionsupporting
confidence: 87%
“…Although interstitial laser therapy (ILT) is less invasive than surgical resection, it appears that ILT as a single treatment modality will fail in those cases in which tumors encroach upon heat-sensitive vital structures [7]. An alternative approach is to deliver laser photothermal emissions to tumors after uptake of light-and heat-sensitive anti-cancer drugs, allowing therapy at reduced thermal energy and elevated intratumor drug levels [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Further in vivo research demonstrated that the antitumor effect of a local cisplatin application can be boosted by laser thermal therapy (9) or by interstitial laser therapy (38). Taken together, LLLT was able to raise the cytotoxicity of the applied drug at nearly every concentration tested, which is known as laser photochemotherapy (39). There is evidence (6 h) that chemotherapeutic agents such as cisplatin are potential candidates for light or heat activation in tumor cells (40).…”
Section: Multiparameter Metabolic Analysis Of Measuring Oxygen Consmentioning
confidence: 99%
“…In addition to the advantage of photo-activation, several of these light sensitive chemotherapeutic agents have been reported to exhibit enhanced toxicity in tumor cells after photo-thermal-activation (Chung et al, 2003;Graeber et al, 1999;Graeber et al, 1998;Paiva et al, 1995;Saxton et al, 1996). As a result, a potentially useful and less invasive approach for treatment of malignancies is to combine imaging guided interstitial laser surgery with conventional chemotherapy (Paiva et al, 2005b;Saxton et al, 1995). Several FDA approved anti-cancer drugs are highly photosensitive or heat-responsive, including anthracycline derivatives and cisplatin Graeber et al, 1999).…”
Section: Introductionmentioning
confidence: 99%